Education as a philosophical and legal category - Elena V. Bestaeva; Elena Y. Grishnova; Ludmila Yu. Grudtsina; Oksana R. Doguzova; Natalia A. Selezneva (Revista on line de Política e Gestão Educacional)
The purpose of the article is to study the essence and content of the "education" concept as a philosophical category in the historical aspect, as well as from a legal point of view. The leading method of studying the problem was the deductive method, which allowed studying the category of education as a historical and philosophical-legal one in the socio-cultural system, with the disclosure of the problem of the autonomy of education in the aspect of politics and economics. The article proves that a comprehensive, generalized analysis of the Russian pedagogical thought of the 19th century, its composition, structure, specifics, its main ideas and problems, its place in the general development of Russian pedagogy is the most important task of future historical and pedagogical research. To facilitate the implementation of this task as much as possible, we will draw attention to several unresolved problems that are not explained in historiography and what prevents their solution.